2019
DOI: 10.1021/acsami.9b05131
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Hybrid Materials Based on Natural Spider Silk

Abstract: Spider silk is a natural material possessing unique properties such as biocompatibility, regenerative and antimicrobial activity, and biodegradability. It is broadly considered an attractive matrix for tissue regeneration applications. Optical monitoring and potential control over tissue regrowth are attractive tools for monitoring of this process. In this work, we show upconversion modification of natural spider silk fibers with inorganic nanoparticles. To achieve upconversion, metal oxide nanoparticles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 77 publications
0
18
0
1
Order By: Relevance
“…L. fallax was chosen as the producer of the model material in this work because its silk was recently demonstrated to be attractive as a tissue engineering material with beneficial biointernalization characteristics. 82 It is a Bolivian curtain-web spider with an enlarged abdomen that makes up half of the spider’s body. Thus, the amount of silk produced is substantially larger than that of typical orb-web spiders.…”
Section: Resultsmentioning
confidence: 99%
“…L. fallax was chosen as the producer of the model material in this work because its silk was recently demonstrated to be attractive as a tissue engineering material with beneficial biointernalization characteristics. 82 It is a Bolivian curtain-web spider with an enlarged abdomen that makes up half of the spider’s body. Thus, the amount of silk produced is substantially larger than that of typical orb-web spiders.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the upconversion luminescent properties of these nanoparticles could be extended to the macroscale components of the fibrous hybrid while the spidroin backbone remains unaffected. Such spider silk–inorganic nanoparticle-based hybrid materials may have prospective bio-applications in the fields of biosensing and bioimaging in a non-invasive and real-time manner (Kiseleva et al, 2019 ).…”
Section: Fabrication Of Spider Silk-based Hybrid Materialsmentioning
confidence: 99%
“…Additionally, metal oxides suit well for the preparation of upconverting luminescent materials as matrices for doping owing to their chemical and photochemical stability, high refractive indices and low phonon energies [ 92 , 93 ]. As such, due to the modification of native spider silk fibers with nanoparticles of zirconia (ZrO 2 ) and hafnia (HfO 2 ) doped with rare earth elements, upconversion luminescent properties of the nanoparticles were extended to macro-scale components of the fibrous hybrids while the obtained materials remained biocompatible [ 94 ]. These optically active hybrid materials based on spider silk and inorganic nanoparticles may find applications in the fields of biosensors and bio-imaging in a noninvasive and real-time manner.…”
Section: Modification Of Spider Silk By Inorganic Nanomaterialsmentioning
confidence: 99%